Development of International Training Guide Abroad for Lecturers of Education Management Department State University of Surabaya - Ima Widiyanah; Dian Anggraini; Maya Rizki Amalyasari (CV. Edutechnium Indonesia, 2023)
This study is a development that aims to develop international training guides abroad for lecturers in the Education Management Study Program to help prepare lecturers to take part in international training programs. The obstacle in the field is that the management of international training activities abroad for Education Management lecturers is not optimal and still encounters obstacles. The obstacles faced include 1) communication between participants and program coordinators that have not been running effectively, 2) suboptimal preparation of participants in carrying out activity programs abroad, 3) the implementation of mentoring activities has not run optimally, 4) evaluation activities have not been carried out on an ongoing basis. This research method uses R & D (research and development), a research approach to conduct research, development, and product testing based on needs analysis. The study results show that the development results in international training guidelines abroad show that 88.5% are feasible to be applied. As evidenced by the results of the questionnaire of experts and model users, which include model elements, content suitability, constructs, language, practicality, and writing organization, obtaining an average score of 82.8% is very valid to be used in Education Management Study Program, Universitas Negeri Surabaya.